2017
DOI: 10.1371/journal.pone.0188979
|View full text |Cite
|
Sign up to set email alerts
|

Do early neural correlates of visual consciousness show the oblique effect? A binocular rivalry and event-related potential study

Abstract: When dissimilar images are presented one to each eye, we do not see both images; rather, we see one at a time, alternating unpredictably. This is called binocular rivalry, and it has recently been used to study brain processes that correlate with visual consciousness, because perception changes without any change in the sensory input. Such studies have used various types of images, but the most popular have been gratings: sets of bright and dark lines of orthogonal orientations presented one to each eye. We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 125 publications
(156 reference statements)
0
1
0
Order By: Relevance
“…In modern science, researchers found that oriented lines or objects contribute significantly to visual perceptions [ 7 , 8 ]. Under certain circumstances, the lines and line orientations in an image affect people’s perception, behavior, and even decision-making [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In modern science, researchers found that oriented lines or objects contribute significantly to visual perceptions [ 7 , 8 ]. Under certain circumstances, the lines and line orientations in an image affect people’s perception, behavior, and even decision-making [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%